2016
DOI: 10.1589/jpts.28.3030
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of effective methods for measuring and stretching for pectoral muscle tightness in breast cancer patients

Abstract: [Purpose] To evaluate differences in pectoral muscle tightness according to arm abduction angle and to determine the best arm abduction angle for stretching of pectoral muscle tightness in breast cancer patients. [Subjects and Methods] Horizontal abduction differences of shoulders were measured bilaterally by arm abduction to 45°, 90°, and 135° to determine the best arm abduction angle for measuring pectoral muscle tightness. Thirty-two patients were divided into three pectoral muscle stretching groups (A: 45°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several studies have indicated the possible contribution of the pectoral muscles to pain and upper limb dysfunctions after breast cancer treatment. 3,[8][9][10] In the acute treatment phase of the cancer, breast and axillary surgery and radiotherapy cause scar tissue formation, wound healing, fibrosis and shortening of soft tissues, such as the pectoral muscles. 3,[8][9][10] Initially, this may lead to an increase in muscle tone of the pectoral muscles and local postoperative or post-radiotherapy pain.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated the possible contribution of the pectoral muscles to pain and upper limb dysfunctions after breast cancer treatment. 3,[8][9][10] In the acute treatment phase of the cancer, breast and axillary surgery and radiotherapy cause scar tissue formation, wound healing, fibrosis and shortening of soft tissues, such as the pectoral muscles. 3,[8][9][10] Initially, this may lead to an increase in muscle tone of the pectoral muscles and local postoperative or post-radiotherapy pain.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3,[8][9][10] In the acute treatment phase of the cancer, breast and axillary surgery and radiotherapy cause scar tissue formation, wound healing, fibrosis and shortening of soft tissues, such as the pectoral muscles. 3,[8][9][10] Initially, this may lead to an increase in muscle tone of the pectoral muscles and local postoperative or post-radiotherapy pain. 3,10 In a further postoperative stage, forward shoulder position, induced by the shortened, hypertonic pectoral muscles and narrowing of the subacromial space may lead to rotator cuff pathologies, which can be painful and contribute to upper limb dysfunctions as well.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The onset of upper limb impairments can be explained by changes in the pectoral muscles after treatment for breast cancer, among others. (Stubblefield and Keole, 2013, Hidding et al, 2014, De Groef et al, 2015, Lee et al, 2016 Several studies describe an increased muscle tone and shortening of the pectoralis major muscle after breast cancer treatment. (Shamley et al, 2009) (Hage et al, 2014) Both tissue removal during surgery and post-radiotherapy fibrosis may enhance this.…”
Section: Introductionmentioning
confidence: 99%